Digital PFM and Reporting Quality in Local Governments: Systematic Review and Framework - Agus, Agus Kurniawan (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
This article presents a systematic literature review (2021–2025) on public sector accounting in local governments and develops a conceptual framework that integrates accrual-based reporting reforms with digital public financial management (FMIS, e-budgeting, e-procurement, and open fiscal data). The review identifies four dominant themes: (i) accrual reform maturity and reporting quality, (ii) data governance and system interoperability, (iii) auditability and the rise of analytics-enabled assurance, and (iv) citizen-centred transparency and public value. Synthesised evidence suggests that digitalisation improves reporting quality only when supported by internal control, standardised data, and capable human resources. We propose testable propositions linking institutional pressures and resources to accounting-system quality, audit outcomes, and public accountability in local governments.